The host rock of the central Patagonian batholith in Gastre: Further insights on the late Triassic to early Jurassic deformation in the region - Zaffarana, C.B. (2012)
Small outcrops of biotitic-amphibolic schists and amphibolites found in two localities suggest that the Cushamen Formation is host rock of the Central Patagonian Batholith in Gastre. The characteristics of these rocks were investigated using structural, petrographic, magnetic fabric, and garnet chemical-zonation studies. Garnet is observed as a late product of contact metamorphism. Structural data from the studied area and from other localities in the region are in conflict with models that invoke the occurrence of uniform, large-scale dextral displacements along the Gastre lineament in Mesosoic times. Rather, the data suggest that the Gastre granitoids record heterogeneous low-temperature deformation of likely Late Triassic age. This low-temperature deformation appears as small, localized outcrops, and we suggest that it is related to the accommodation of the successive magma batches that built the Central Patagonian Batholith.